The evolution of concepts governing state–church relations across the centuries. An outline of the Issues in the context of Polish historical experience - Bernaciński, Łukasz (A thousand years of Poland’s presence among the elite of European states, 2026)
This study is devoted to the evolution of the attitude of states toward the phenomenon of religiosity. Particular emphasis is placed on presenting these changes against the backdrop of Polish state history. The aim of the study is to verify the thesis that Poland has belonged for a thousand years to the select group of states that have remained at the forefront of the legal protection of religious freedom — both in its individual and collective dimensions. The research conducted has allowed for the formulation of the thesis that there exists a close relationship between the constitutional principles governing the Polish state's approach to religious communities and the teaching of the Catholic Church as current in any given historical period. The only periods of departure from this rule proved to be the times of foreign partitions and occupation, when Poles had no real influence over the shaping of law in their own country.